"Things Done Changed": Recalibrating the Real in Hip-Hop. Issue 4 (8th August 2021) - Forman, Murray
ABSTRACT: This paper critically engages the ways in which hip-hop artists and scholars have commonly defined authenticity and "the real" in relation to Black male identities with an emphasis on the dominant representations of the real associated with the "gangsta" persona. In a crucial shift, however, open discussion about mental health and Black social existence has helped to unravel prior concepts of unyielding masculinity, facilitating the public expression of Black interior reflection and contributing to a radically revised, post-gangsta conceptualization of "the real" in hip-hop.